PEMAHAMAN MAHASISWA TERHADAP IDE BISNIS DAN KONSEP KEUANGAN DALAM PEMBELAJARAN KEWIRAUSAHAAN - Dina Mariana Uli Lubis (Politeknik ATK Yogyakarta, 2020)
The establishment of micro, small and medium enterprises has an important role in the country's economy because it is able to provide jobs and drive the country's economy. Polytechnic of Yogyakarta ATK as one of the Vocational education institutions that educate the nation's young generation gives encouragement to students to have the spirit to become entrepreneurs. One of them is by giving entrepreneurship courses. To start a new business requires a viable business idea as a business opportunity. Entrepreneurs also need an understanding of the concept of finance for the sustainability of the business they have established. In learning entrepreneurship, Polytechnic of ATK Yogyakarta students has been able to understand business ideas so that they are able to emerge about business ideas and are able to identify the most possible business opportunities to do. And already have an understanding of the concept of finance, in this case, the financial statements such as balance sheets, income statements, and cash flow statements. With an understanding of business ideas and financial concepts, it is hoped that Polytechnic of Yogyakarta ATK students can become entrepreneurs by establishing a business when they graduate from the Polytechnic of ATK Yogyakarta.